Book Development of Volley Ball Passing Variations in the Special Preparation Period for Volley Ball Teachers and Coaches in Palembang - Ilham Dwi Alamsyah; Bangkit Seandi Taroreh (UNIB Press, 2022)
This study aims to develop a volleyball passing variation book during the special preparation period for volleyball teachers and coaches. This research uses the ADDIE model development research method which consists of 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data collection techniques using a questionnaire. Data analysis used quantitative descriptive analysis. Product validation was carried out by five experts consisting of one volleyball learning expert, one language expert, 2 volleyball coaches and 1 volleyball extracurricular teacher in high school. The research sample was taken through a purposive sample of 23 people. The results showed that the book of volleyball passing variations in the special preparation period for volleyball teachers and coaches in Palembang has gone through expert validation with the results of the book's grammatical suitability of 89.3% (category very worth using), the ease of using the book is 86.5% (category very worth using), the suitability of the material is 90.3% (category very worth using) and the result of book implementation is 86.5% (category very worth using).